The Bromine, Calcium, Potassium, Magnesium, Manganese, and Sodium Contents in Adenocarcinoma of Human Prostate Gland - Vladimir Zaichick; Sofia Zaichick (Journal of Hematology and Oncology Research, 2016)
Objectives: Adenocarcinoma of prostate is an internationally important health problem of the man, particularly in developed countries. The aim of this exploratory study was to evaluate whether significantchanges in the prostatic tissue levels of calcium (Ca), potassium (K), and magnesium (Mg) as an androgen dependent chemical element, and bromine (Br), manganese (Mn), and sodium (Na), as androgen independent elements, exist in the malignantly transformed prostate. Methodology: Prostatic tissue levels of Br, Ca, K, Mg, Mn, and Na contents were prospectively evaluated in 10 patients with adenocarcinoma and 37 healthy male inhabitants. Measurements were performed using non-destructive instrumental neutron activation analysis with high resolution spectrometry of short-lived radionuclides. Tissue samples were divided into two portions. One was used for morphological study while the other was intended for chemical element analysis. The reliability of difference in the results between normal and cancerous prostate tissues was evaluated by Student’s t-test. Key Results: Mean values ± standard error of means (M±SΕΜ) for mass fraction (mg/kg on dry mass basis) of chemical element in the normal tissue were:Br32.9±3.6, Ca 2280±178, K 11211±414, Mg 1118±76, Mn 1.24±0.07, and Na 11100±408, respectively. The contents of Br and Mn were significantly higher (approximately 4 and 6 times, respectively) while those of Ca and Mg (nearly 3 times) and K and Na (20% and 30%, respectively) were significantly lower in cancerous tissues than in normal tissues. Major Conclusions: In adenocarcinoma transformed prostate tissue the chemical element metabolism is significantly disturbed.
Keywords: Chemical elements